Pelecehan Seksual: Analisis Faktor Penyebab, Dampak terhadap Korban, dan Tinjauan Pendidikan Seksualitas Menurut Familiaris Consortio - Petrus Damianus Bheo (JURNAL PASTORAL KATEKETIK, 2026)
Sexual harassment is a serious issue that threatens human dignity and has become an alarming phenomenon in modern social life. This study aims to analyze the factors that cause sexual harassment, examine its impact on victims, and assess the role of sexuality education according to the teachings of the Catholic Church, particularly the document Familiaris Consortio. The research was conducted using a qualitative method with a literature review approach. Data sources were gathered from various academic literature, journal articles, Church magisterial documents, and previous research findings. The results of the study indicate that sexual abuse is triggered by various factors, such as weak self-control, abuse of power, media influence, and a lack of moral and spiritual education. Its impact is not only felt individually by the victims but also has broader social consequences. From the perspective of Church teaching, particularly Familiaris Consortio, sexuality education is viewed as an integral process of personal formation, not merely conveying biological information, but also instilling values of love, responsibility, fidelity, and respect for the dignity of the human body. Therefore, proper sexuality education needs to be developed from an early age within the family and educational environments, as a preventive strategy to form morally mature individuals capable of building healthy and humane relationships.